2010
DOI: 10.1051/0004-6361/201015166
|View full text |Cite
|
Sign up to set email alerts
|

Spectra disentangling applied to the Hyades binaryθ2   Tauri AB: new orbit, orbital parallax and component properties

Abstract: Aims. θ 2 Tau is a detached and single-lined interferometric-spectroscopic binary as well as the most massive binary system of the Hyades cluster. The system revolves in an eccentric orbit with a periodicity of 140.7 days. Its light curve furthermore shows a complex pattern of δ Scuti-type pulsations. The secondary has a similar temperature but is less evolved and fainter than the primary. In addition, it is rotating more rapidly. Since the composite spectra are heavily blended, the direct extraction of radial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…9) considered by . Torres et al (2011) determined a new orbit for θ 2 Tau, an orbital parallax of 20.90 ± 0.14 mas and component masses M A = 2.86 ± 0.06M and M B = 2.16 ± 0.02M . Combined Mark III and NPOI analyses were completed for: ζ 1 UMa or Mizar (Fig.…”
Section: Mark III Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…9) considered by . Torres et al (2011) determined a new orbit for θ 2 Tau, an orbital parallax of 20.90 ± 0.14 mas and component masses M A = 2.86 ± 0.06M and M B = 2.16 ± 0.02M . Combined Mark III and NPOI analyses were completed for: ζ 1 UMa or Mizar (Fig.…”
Section: Mark III Resultsmentioning
confidence: 98%
“…Another example is the system η And (Fig. In order to refine the orbital solution for θ 2 Tau, by performing a combined astrometric and spectroscopic analysis based on the new spectroscopy and longbaseline data from the Mark III optical interferometer, Torres et al (2011) determined a new orbit for θ 2 Tau, an orbital parallax of 20.90 ± 0.14 mas and component masses M A = 2.86 ± 0.06M and M B = 2.16 ± 0.02M , the mass ratio being in good agreement with the older estimates of Peterson et al (1991), Peterson et al (1993), but the mass of the primary being 15-25% higher than the more recent estimates by Torres et al (1997) and Armstrong et al (2006). They found M A = 2.59 ± 0.30M and M B = 2.34±0.22M for the component masses and 76 ± 2 pc for the distance to η And.…”
Section: Mark III Resultsmentioning
confidence: 99%
“…It is notable that in their detailed study of another evolved A-type binary with eccentric orbit, θ 2 Tau, Torres et al (2011) also found the projected rotational velocity for the secondary roughly twice as high as for the primary.…”
Section: A Comparison With Synthetic Spectra and The Rotation Of The mentioning
confidence: 97%
“…Ainda nesta figura, os pontos indicam os valores medidos de velocidades radiais, enquanto que as curvas sólidas indicam os melhores ajustes para os pontos obtidos. Os astrônomos investigadores deste sistema binário estimaram o período orbital em aproximadamente 140 dias [17]. Podemos notar também que as curvas de velocidades radiais para este sistema não são simétricas ou não possuem os formatos simples de senos e cossenos, indicando que á orbitaé bem excêntrica, ou seja, está bem distante do formato circular.…”
Section: As Estrelas Binárias Espectroscópicasunclassified